Da açudagem e transposições às tecnologias sociais: territorialização e conflitos entre as políticas públicas de enfrentamento à seca e convivência com o semiárido nos estados da Paraíba e de Pernambuco - Araújo Segundo Neto, Francisco Vilar de (2022)
During the historical process of formation of the semi-arid region, several public policies were developed in order to "combat" the effects of droughts in the region. However, despite the major interventions and impacts caused, the problems related to droughts continued to plague the population. It was necessary to adopt new actions and policies, because there was no way to end the droughts, but it was possible to live with it. This thesis seeks to analyze the conflicts between public policies aimed at water resources (plate cisterns of the Programa Um Milhão de Cisternas / Programa Cisternas versus polyethylene cisterns of the Programa Água Para Todos) in the Brazilian semi-arid region, their paradigms and their territorializations. The spatial scope of this research comprised the states of Paraiba and Pernambuco. To carry out this work, the actions and projects proposed in the field of public policies aimed at water resources in the semi-arid region were analyzed in the geospatial and conceptual field, as well as in the actions developed by civil society, supported by the existing logic in its various proposals. In this way, it was possible to evaluate the territories demarcated by water issues, observing all the subjects involved to understand the essence of the phenomena that generate the process of territorial formation, where the water resource is a conditioning element in the constitution of these spaces. According to the results presented, within the scope of the Programa Um Milhão de Cisternas, it can be seen that its performance in the state of Paraiba is stronger than in Pernambuco in terms of percentage of people served, even if in absolute numbers of quantity of cisterns the picture is the opposite. On the other hand, when it comes to cisterns financed by the MDS and from the Programa Cisternas, the situation is reversed, with a strong participation of state and municipal political spheres in the process of implementing social technologies in the state of Pernambuco. On the other hand, in the context of the Programa Água Para Todos (PAT), between 2011 and 2014, this policy was responsible for the installation of 5,000 polyethylene cisterns in the state of Paraiba and just over 47,000 in Pernambuco, with DNOCS and Codevasf as the responsible bodies. This thesis concludes that the impact of the PAT, through polyethylene cisterns, was negligible in Paraiba and reasonably significant in Pernambuco. These policies, both the coexistence with the semi-arid region and the universalization of access to water, through plate cisterns (P1MC) and polyethylene cisterns (PAT) respectively, were simultaneous for years. Although they coexisted, they denied each other. Their spatial coexistence was conflicting, as they started from different principles that led to different paradigms, building different territories. While the plate cisterns are the starting point for the practices of coexistence with the semi-arid, the polyethylene cisterns go back to the policies to combat droughts.